PERAN KUALITAS PELAYANAN TERHADAP KEPUASAN LAYANAN MELALUI KINERJA PEGAWAI SEBAGAI VARIABEL INTERVENING PADA BPPRD KOTA METRO - Ariyanti, Siti Iftiyah; Febriyanto, Febriyanto; Sigalingging, Marhaban (Universitas Muhammadiyah Metro, 2025)
This research was conducted because BPPRD Metro City has the main task of carrying out several government affairs related to public services, so it is necessary to examine how satisfaction with employee services is provided. This research aims to determine whether service quality through employee performance as an intervening variable influences service satisfaction. This research uses a quantitative analysis method with associative descriptive research. The population in this study were people who used BPPRD Metro City services in July 2023, totaling 122 people. The sample in this study was selected using the Solvin formula so that 93 respondents were obtained. Data collection techniques were carried out using observation, questionnaires, and documentation. Data analysis techniques use simple regression and path analysis. The results of this research are (1) a significant influence between Service Quality and Employee Performance, as evidenced by the calculated t value of 3.50 > t table 1.665. (2) there is a significant influence between service quality and service satisfaction, as evidenced by the calculated t value of 3.648 > t table 1.665. (3) there is a significant influence between employee performance on service satisfaction, as evidenced by the calculated t value of 8.519 > t table 1.665. (4) indirectly, service quality through employee performance has a significant influence on service satisfaction, as evidenced by the direct influence value of 0.145 < the indirect influence value of 0.2119